STUDY OF THE POLYPHENOLS CONTENT IN THE VARIOUS APPLES SORTS OF THE KAZAKHSTAN SELECTION - Alibekov, Ravshanbek (Academic Scientific Journal of Chemistry, 2022)
All polyphenolic compounds, including phenolic and flavonoid varieties, are divided into groups according to the structure and type of fragment. About 10000 types of various structures of polyphenolic compounds are known that are found in plants and food products. However, a lot of plants species are not properly studied so far. The range of orchards in Kazakhstan is quite diverse and it is represented by well-known ancient and new domestic selection with excellent quality that are very adaptable for the growing conditions. For the study content of physico-chemical indicators and biologically active substances, in particularly the amount of total phenolic content and total flavonoids content, following winter apples sorts were selected: "Talgarskoe", "Voskhod", "Sarkyt", "Saya", "Baiterek". It was found that in comparison among them, "Sarkyt", "Saya" and "Baiterek" have the best physico-chemical indicators in the Solids content, Total sugars and Titratable acidity, Sugar-acid index, Ascorbic acid (vitamin C) content, Total phenolic content and Total flavonoids content. The polyphenols content in all apple sorts have highest indicators, in average ± 12 μg/mL. Among them, “Baiterek” excels by highest values and it was found as promising apple sort. As well in the considering of the Total flavonoids content, values of “Sarkyt”, “Saya” and “Baiterek” are higher than “Talgarskoe” and “Voskhod” in average 2-3 times more. The extracts of these mentioned apples have high rates in biologically active substances, could be recommended for creation in the production of concentrate technology and in the enrichment of the composition of food products.